Relationship Between Supervising the Head of the Room and Hand Washing at Siloam Dhirga Surya Hospital Medan - Elyani Sembiring (Institute of Computer Science (IOCS), 2020)
Hand washing is a intervention which as not important by nurses, but it is a really important thing to prevent nosocomial infection in hospital. Supervision assumed with relationship with intervention by nurses for hand washing. The research applied correlation analytic design with cross sectional approach. The location of the research was Siloam Dhirga Surya Hospital Medan. The research population were 77 respondents, taken by using total sampling technique. Data analysis with univariate and bivariate methods and using chi-square test with significant level 95% (α = 0.05). The results showed that 71.4% of supervision performed by ward heads was good, 28.6% of supervision performed by ward heads was less good. Nurses performed good hand washing (66.2%), and nurses performed less good hand washing (33.8%). It was concluded that any correlation between the ward heads’ supervision and nurses’ hand washing (p value=0.000). More good supervision by ward head and then more good nurses performed hand washing. It is recommended that the hospital management improve nurse behavior in performing hand washing to prevent from nosocomial infection.